Frank T. Sands papers - Sands, Frank T.
Contract (1862 May 5) between Sands and the U.S. government for the burial of soldiers; business card; photographs of Sands; and newspaper clippings relating to Sands's descendants' claim that he was the undertaker for Abraham Lincoln and William Wallace ("Willie") Lincoln.
In part, typewritten transcript.
Undertaker of Washington, D.C.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Death and burial; Lincoln, William Wallace, -- 1850-1862 -- Death and burial; Burial -- Washington (D.C.); Undertakers and undertaking -- Washington (D.C.); Undertakers